Flexible learning implementation of higher educationa institution in La Union - Barde, Al Gerald S. (Saint Louis College, City of San Fernando, La Union : [s.n.], 2023)
The effects of the Covid-19 pandemic have forced higher education institutions to explore innovative learning modalities such as flexible learning that students' needs for more flexibility and autonomy in shaping their learning process. This study assessed the flexible learning implementation of higher education institutions in La Union along three (3) areas namely learning materials and modality; resources and support services for students, and resources and support services for faculty and non-academic staff. This study used mixed methods in research more specifically the sequential explanatory approach to determine and analyze the level of flexible learning implementation. A ready-made rubric developed by the Commission on Higher Education (CMO 32, s. 2021) was used as an assessment tool to determine to determine the level of FL implementation of 16 HESs in La Union. After, the researcher analyzed their Learning Continuity Plans and responses to the interview questions to support their level of FL implementation. Findings showed that HEI were at the developing level which means that some key items in the CMO 4, s. 2020 of the Guidelines in the Implementation of Flexible Learning were not yet fully implemented. Furthermore, this study revealed that the HEIs struggled in developing and providing resources and support services for both the students and personnel. An action plan designed by the researcher was recommended to guide CHEDROI is providing assistance to HEIs to address the challenges in their implementation of flexible learning.
References: pages 164-186.
CHED-La Union
Keywords: Higher education